Um Olhar para a (Re)Constituição de Práticas Culturais de Estudantes com a Internet em um Ambiente Híbrido - Barros, Ana Paula Rodrigues Magalhães de [UNESP]; Maltempi, Marcus Vinicius [UNESP] (UNESP - Universidade Estadual Paulista, Pró-Reitoria de Pesquisa; Programa de Pós-Graduação em Educação Matemática, 2022)
Teaching and learning practices have specific characteristics grounded on the contexts in which these practices are constituted. However, in environments with Internet access, practices that ignore such characteristics are not uncommon. The aim of this article is to identify characteristics and contributions of the (re)constitution of students’ cultural practices with the Internet in a hybrid environment. The qualitative research took place in a first-year high school class at a Technical State School, in Nova Odessa (SP). A hybrid environment was created to conduct lessons about functions. Data was collected in an online learning environment on Facebook and in in-person meetings. From a complexity perspective, narrative inquiry was adopted for the interpretation and analysis of data gathered in four-day school episodes. The emergence of learning collectives was identified as the main characteristic. These collectives presented practices that involved skills such as researching and negotiating meaning about students’ own responses. Understanding the (re)constitution of cultural practices in hybrid environments contributes to teacher actions and decision-making that consider students' skills and needs; it contributes also for hybrid models not to be adopted as sufficient.

Práticas de ensinar e aprender possuem características específicas dos contextos em que são constituídas, entretanto, em ambientes que oferecem acesso à Internet , são comuns práticas que as ignoram. Diante disso, o objetivo deste artigo é identificar características e contribuições da (re)constituição das práticas culturais de estudantes com a internet em um ambiente híbrido . A investigação, de natureza qualitativa, ocorreu em uma turma da primeira série do Ensino Médio de uma Escola Técnica Estadual, em Nova Odessa (SP), onde foi constituído um ambiente híbrido para o estudo do conceito de Função. Os dados foram produzidos em ambiente online de aprendizagem ( Facebook ) e em encontros presenciais. A análise narrativa foi adotada para a interpretação e análise dos dados produzidos em episódios de quatro dias letivos, sob a perspectiva da complexidade. A principal característica identificada foi a emergência de coletivos de aprendizagens com práticas que envolveram habilidades de pesquisar e negociar sentidos sobre as respostas produzidas pelos estudantes. A compreensão da (re)constituição das práticas culturais no ambiente híbrido contribui para que ações docentes e tomadas de decisões considerem as habilidades e necessidades dos estudantes e para que modelos híbridos não sejam adotados como suficientes.
The (Re)Constitution of Students’ Cultural Practices in a Hybrid Environment within Mathematics Classes
Keywords: Mathematics Classes; Classroom; Complexity; Teaching and Learning Practices; Functions; Aulas de Matemática; Sala de Aula; Complexidade; Práticas de Ensinar e Aprender; Funções